Menuju Sanitasi Aman 2045 : Peran Strategis Pemerintah Provinsi Banten dalam Pengelolaan Air Limbah Domestik: Towards Safely Managed Sanitation by 2045: The Strategic Role of the Banten Provincial Government in Domestic Wastewater Management - karvina budiwati apriliani; Arlan Marzan; Isvan Taufik; Windu Iwan Nugraha; Resti Meiliana Sari (Jurnal Teknologi Lingkungan, 2025)
The rapid population growth and urbanization in Banten Province have led to a significant increase in domestic wastewater generation. As of 2024, access to basic sanitation services has reached 88.7%; however, access to safely managed sanitation remains at only 20.1%, still below the national target of 90% as outlined in the 2020–2024 National Medium-Term Development Plan (RPJMN). This study aims to identify the strategic role of the Provincial Government of Banten in managing domestic wastewater across regencies and municipalities by employing juridical-empirical, spatial, and institutional approaches. Projections indicate an increase in wastewater generation from 12,786 liters/second in 2024 to 19,311 liters/second by 2044, and faecal sludge volumes from 1,807 m³/day to 2,742 m³/day over the same period. Development Work Area 1 (WKP 1) has been identified as the focal point for regional SPALDT and IPLT infrastructure due to its high population density and waste load. The main contribution of this study lies in the integration of spatial planning, regulatory frameworks, and fiscal capacity in regional sanitation planning an area still underrepresented in Indonesian literature. The findings highlight the critical role of the Provincial Government as a facilitator in achieving 70% coverage of safely managed sanitation by 2045.